(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This research analyzes the simplification of customs clearance processes in food imports, specifically focusing on the economic prospects of digitalizing "Green" customs corridors. The relevance of the study is determined by the necessity to reduce the clearance time for perishable food products at border crossing points and to ensure national food security. The author scientifically substantiates mechanisms to reduce excess expenditures by improving artificial intelligence-based risk management systems. Furthermore, the study evaluates the impact of the digital declaration system on supply chain efficiency and proposes practical recommendations for minimizing errors in the customs clearance process, as well as integrating phytosanitary and veterinary controls into a single digital platform.